2021
DOI: 10.1016/j.scib.2020.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of SARS-CoV-2 main protease in complex with the natural product inhibitor shikonin illuminates a unique binding mode

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 10 publications
1
50
0
Order By: Relevance
“…Among the known M pro inhibitors, the majority of them are covalent inhibitors such as GC376 analogs that contain a pyrollidone in the P1 position as a glutamine mimetic. Several structurally distinct compounds including ebselen, disulfiram, carmofur, PX-12, tideglusib, and shiknonin were claimed as M pro inhibitors 16,17 , but were later invalidated as promiscuous non-specific cysteine protease inhibitors 18,19 . In addition, non-covalent inhibitors such as ML188 (R) were developed and validated as SARS-CoV M pro inhibitors 5,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the known M pro inhibitors, the majority of them are covalent inhibitors such as GC376 analogs that contain a pyrollidone in the P1 position as a glutamine mimetic. Several structurally distinct compounds including ebselen, disulfiram, carmofur, PX-12, tideglusib, and shiknonin were claimed as M pro inhibitors 16,17 , but were later invalidated as promiscuous non-specific cysteine protease inhibitors 18,19 . In addition, non-covalent inhibitors such as ML188 (R) were developed and validated as SARS-CoV M pro inhibitors 5,12 .…”
Section: Discussionmentioning
confidence: 99%
“…2c).Consistent with the design hypothesis, several compounds including 14, 17, 18, 19, 20, 21, and 23 had significantly improved enzymatic inhibition (IC 50 < 3 µM) compared to compound 13.Replacing the tert-butyl in compound 13 with the bulkier trimethylsilyl led to compound 14 with a 2.9-fold increase in M pro inhibition. Cyclohexyl(17), thienyl (19), pyrrolyl(20), pyridinyl(21), and phenyl(23) were found to be the most favorable substitutions at the S2 pocket. Compound 16 with piperidyl substitution had similar potency as compound 13, while compound 15 with O-tert butyl was less active.…”
mentioning
confidence: 94%
“…3 A and B) and generated various different views of the overall structure of SARS-CoV-2 M pro in complex with shikonin ( Fig. 3 C) ( Li et al, 2020a ). Li et al demonstrated that the catalytic dyad His41 and Cys145 residues undergo huge conformational changes, creating a striking difference with other reported structures ( Dai et al, 2020 ; Zhang et al, 2020e ).…”
Section: Promising Active Ingredients Of Chinese Herbal Medicine Thatmentioning
confidence: 99%
“…Li et al demonstrated that the catalytic dyad His41 and Cys145 residues undergo huge conformational changes, creating a striking difference with other reported structures ( Dai et al, 2020 ; Zhang et al, 2020e ). Further analysis of the shikonin binding pocket revealed three novel interactions (π-π interactions with the His41 residue, hydrogen bond interactions with the Gln189 and Thr190 residues, and hydrogen bond interactions with the Met165, His164, and Cys145 residues) ( Li et al, 2020a ). This study demonstrated different binding patterns, thus suggesting significant diversity in terms of binding sites.…”
Section: Promising Active Ingredients Of Chinese Herbal Medicine Thatmentioning
confidence: 99%
See 1 more Smart Citation